E-waste Management Practices: A Case of Itahari Sub-Metropolitan City, Nepal - Rauniyar, Bishnu Shau (Journal of Vishwa Adarsha College, 2024)
The fast deterioration of electronic gadgets is being caused by the highly competitive electronic market and the rising purchasing patterns of consumers. It can be difficult to handle electronics when their useful lives are ending and when they are replaced or thrown away for various reasons over time. This research aims to comprehend the viewpoint of electronics consumers regarding managing their electronic waste, with a particular focus on Itahari Sub-Metropolitan City's ward no. 05. The factors found in the literature were used to create questionnaires. The questions were created using various sources, including socioeconomic and demographic data, information on E-waste generation and disposal practices, consumer intentions toward E-waste management, and awareness levels. The study's findings demonstrated that while consumers were aware of the issues surrounding E-waste, they lacked a significant amount of knowledge regarding formal recycling centers and other strategies for managing waste. Additionally, it was seen that most respondents were either willing to sell their televisions and desktop computers to scrap traders or wanted to repair them. For instance, the majority of participants reported never receiving any E-waste management training, but many also claimed they would be prepared to pay the E-waste handling organization to participate in E-waste management programs and hence, Itahari Sub-Metropolitan is advised to undertake community-based initiatives to improve E-waste management programs.